Urban regeneration, tourism and neighborhoods of the historic center of Cusco, Cultural Heritage of Humanity. Comparative analysis 1983-2005 - Quispe Gonzáles, Evaristo (2018)
Cultural heritage is a key spectrum in any society. In this context, communities that inhabit historical centers can be considered truly privileged, because the proper management of these assets could eventually lead to increase their quality of life. This exploratory proposal formulates an analysis of several experiences of urban regeneration experienced between 1983 and 2005 in four historical districts of the Historic Center of Cusco (Santa Ana, San Cristobal, San Blas and San Pedro), mainly in the areas cosidered on the List of World Cultural Heritage by UNESCO, which have developed a touristic orientation. This study will contribute to the consolidation of a panoramic view that allows to make an assessment and a systematization of ‘learnt lessons’. It is important to take into account that the neighborhoods San Blas (Tocokachi), San Cristobal (Qolcampata) and Santa Ana (Karmenka) are Inca in their origin, while the San Pedro neighborhood is of colonial origin: its edification responded to the initiative of building a hospital for the natives.